25. Некоторые значения тригонометрических функций

Теорема. \displaystyle \sin{\pi\over 4}=\cos{\pi\over 4}={\sqrt{2}\over 2}.

Доказательство. Так как \displaystyle {\pi\over 4}+{\pi\over 4}={\pi\over 2}, то \displaystyle \sin{\pi\over 4}=\cos{\pi\over 4} (теорема 2).

\displaystyle \sin^2{\pi\over 4}+\cos^2{\pi\over 4}=1\Rightarrow2\sin^2{\pi\over 4}=1\Rightarrow \sin^2{\pi\over 4}={1\over 2} .

Так как \displaystyle {\pi\over 4}\in\left(0;{\pi\over 2}\right), то \displaystyle \sin{\pi\over 4}>0.

\displaystyle \sin{\pi\over 4}={1\over \sqrt{2}}={\sqrt{2}\over 2} .

Теорема.

\begin{array}{l}<br />
\displaystyle \sin{\pi\over 6}=\cos{\pi\over 3}={1\over 2},\\[3mm]<br />
\displaystyle \cos{\pi\over 6}=\sin{\pi\over 3}={\sqrt{3}\over 2} .<br />
\end{array}

Доказательство.

\begin{array}{l}<br />
\displaystyle<br />
\cos{2\pi\over 3}=\cos\left({\pi\over 3}+{\pi\over 3}\right)=\cos{\pi\over 3}\cos{\pi\over 3}-\sin{\pi\over 3}\sin{\pi\over 3}=\\[3mm]<br />
\displaystyle<br />
=\cos^2{\pi\over 3}-\sin^2{\pi\over 3}=\cos^2{\pi\over<br />
3}-\left(1-\cos^2{\pi\over 3}\right)=2\cos^2{\pi\over 3}-1.\\[3mm]<br />
\displaystyle<br />
\cos{2\pi\over 3}=\cos\left(\pi-{\pi\over 3}\right)=-\cos{\pi\over<br />
3}.<br />
\end{array}

\displaystyle\cos{\pi\over 3} — корень уравнения 2x^2+x-1=0.

\displaystyle x_1={1\over 2},x_2=-1.

Так как \displaystyle {\pi\over 3}\in\left(0;{\pi\over 2}\right), то \displaystyle \cos{\pi\over 3}>0\Rightarrow \cos{\pi\over 3}\ne-1\Rightarrow\cos{\pi\over 3}={1\over 2}.

\begin{array}{l}<br />
\displaystyle<br />
\sin{\pi\over 6}=\cos\left({\pi\over 2}-{\pi\over<br />
6}\right)=\cos{\pi\over 3}={1\over 2},\\[3mm]<br />
\displaystyle<br />
\sin{\pi\over 3}=\sqrt{1-\cos^2{\pi\over 3}}=\sqrt{1-{1\over<br />
4}}={\sqrt{3}\over 2},\\[3mm]<br />
\displaystyle<br />
\cos{\pi\over 6}=\sin\left({\pi\over 2}-{\pi\over<br />
6}\right)=\sin{\pi\over 3}={\sqrt{3}\over 2}.<br />
\end{array}

Задачи.

1) Найдите \displaystyle \sin\left(\frac{\pi}{4}+\alpha\right), если \displaystyle \sin\alpha=\frac{3}{5},\alpha\in\left(\frac{\pi}{4};2\pi\right).

2) Найдите \displaystyle {\rm tg}\,\left(\frac{\pi}{4}-\alpha\right), если {\rm tg}\,\alpha=2.

Оставьте свой отзыв

Добавить изображение